The Effect of Sansevieria Plant on Particulate Matter 2.5 Levels in Classroom (KEMAS: Jurnal Kesehatan Masyarakat, 2023)
The Poor physical environment is the main cause of acute respiratory infections that result in death in school children aged 5 to 14 years due to exposure to PM2.5 at school. The improvement of the school’s physical environment from high PM2.5 pollution is to involve the school community in planting Sansevieria Trifasciata as a solution to reducing PM2.5 pollution. This study aims to analyze the significance of differences in the physical environmental conditions of the Ciranjang 1 State Elementary School, Cianjur Regency, on the level of respiratory susceptibility of students seen from PM2.5 levels before and after the placement of Sansevieria Trifasciata. The study used 2 test classes and 1 control class. The study duration was 24 hours with two measurements, namely at the pretest and posttest. Data analysis used the Ancova one-way test followed by the Post-Hock test. The placement of 8 pots of Sansevieria Trifasciata was able to absorb PM2.5 compared to 6 pots of Sansevieria trifasciata. There is an effective and significant absorption of PM2.5 pollutants by placing 8 pots of Sansevieria trifasciata plants in a 49m2 classroom, which is 29µgr/m3 on the respiratory vulnerability level of Ciranjang 1 State Elementary School students, Cianjur Regency.